2004
DOI: 10.1007/s10157-004-0312-0
|View full text |Cite
|
Sign up to set email alerts
|

A low-protein diet concomitant with high calorie intake preserves renal function and structure in diabetic OLETF rats

Abstract: A low-protein diet, despite the worsening hyperglycemia caused by hyperphagia, not only reduced proteinuria but also ameliorated hyperlipidemia in OLETF rats, thereby preserving renal function and structure in diabetic nephropathy, probably via a macrophage-mediated mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Renal lesions in OLETF rats were characterized by thickening of the glomerular basement membrane, mesangial expansion, sclerotic lesions, interstitial fibrosis (29) and interstitial lymphocyte infiltration (30). In this study, histological appearances revealed findings comparable to these observations.…”
Section: Thiamine Mitigated Albuminuria Renal Interstitial Fibrosissupporting
confidence: 81%
“…Renal lesions in OLETF rats were characterized by thickening of the glomerular basement membrane, mesangial expansion, sclerotic lesions, interstitial fibrosis (29) and interstitial lymphocyte infiltration (30). In this study, histological appearances revealed findings comparable to these observations.…”
Section: Thiamine Mitigated Albuminuria Renal Interstitial Fibrosissupporting
confidence: 81%
“…Thus, the treatment strategies for renal failure, including the use of protein-restricted diets [1], have gained increased interest for the treatment of patients with diabetic nephropathy. Despite the few studies that suggest that protein intake restriction fails to improve renal prognosis in type 1 or type 2 diabetic patients with incipient or overt nephropathy[2] and confers renoprotection[3], several findings have demonstrated that a low-protein diet preserves renal function and structure in animal models [4] and in type 2 diabetic patients with macroalbuminuria[5] and improves disease prognosis[6], low-grade inflammation and proteinuria[7] and depressive symptoms[8]. However, there has been increasing concern regarding the risk of the subsequent development of malnutrition due to these diets.…”
Section: Introductionmentioning
confidence: 99%
“…In nonobese and normoglycemic control LETO rats (group NA), protein restriction also improved the increasing rates of UAE induced by higher energy intake. Matsuda et al, 21 using OLETF rats, reported that the lowprotein diet suppressed urinary protein excretion by more than half after 60 weeks of age, even though the rats fed on a low protein diet showed hyperglycemia and higher hemoglobin Aic levels by hyperphagia. In this study, the amount of food consumed was the same among the three subgroups at 28 weeks of age, although a slight increase was observed between rats at 22 weeks and 28 weeks of age in subgroup AP-10.…”
Section: Discussionmentioning
confidence: 96%